Numerical Solution of Fractional Differential Equations by using Fractional Spline Functions. - Hamasalh, Faraidun K.; Muhammad, Pshtiwan O. (Sulaimani Journal for Pure and Applied Sciences, 2015)
In this paper, we consider a new suitable lacunary fractional interpolation with the idea of the spline function of polynomial form, and the method applied to solve linear fractional differential equations. The results obtained are in good agreement with the exact analytical solutions and the numerical results presented by two examples, results also show that the technique introduced here is robust and easy to apply.
Keywords: Fractional integral and derivative; Caputo Derivative; Taylors expansion; Error bound; Spline functions